Peranan Management Public Relations dalam Mempertahankan Citra Perusahaan Jasa Perhotelan: Studi Kualitatif pada Re-Opening Hotel Mandarin Oriental, Jakarta - Aryanti Puspokusumo (Bina Nusantara University, 2011)
The purpose of this research is to identify implementation of image building and public relations that has been done by MOJKT in HI roundabout in Jakarta that took part in hotel service. Theories that used are communication management theory, PR theory, and image theory. Those theories will be connected with the analysis result in the field. The research method used is qualitative descriptive using analysis method of 6 stages of Public Relations Plan.